Mitochondrial Proteome of Affected Glutamatergic Neurons in a Mouse Model of Leigh Syndrome - Gella, Alejandro; Prada-Dacasa, Patricia; Carrascal, Montserrat; Urpi, Andrea; González-Torres, Melania; Abian, Joaquin; Sanz, Elisenda; Quintana, Albert (Frontiers in Cell and Developmental Biology, 2020)
Defects in mitochondrial function lead to severe neuromuscular orphan pathologies known as mitochondrial disease. Among them, Leigh Syndrome is the most common pediatric presentation, characterized by symmetrical brain lesions, hypotonia, motor and respiratory deficits, and premature death. Mitochondrial diseases are characterized by a marked anatomical and cellular specificity. However, the molecular determinants for this susceptibility are currently unknown, hindering the efforts to find an effective treatment. Due to the complex crosstalk between mitochondria and their supporting cell, strategies to assess the underlying alterations in affected cell types in the context of mitochondrial dysfunction are critical. Here, we developed a novel virus-based tool, the AAV-mitoTag viral vector, to isolate mitochondria from genetically-defined cell types. Expression of the AAV-mitoTag in the glutamatergic vestibular neurons of a mouse model of Leigh Syndrome lacking the complex I subunit Ndufs4 allowed us to assess the proteome and acetylome of a subset of susceptible neurons in a well characterized model recapitulating the human disease. Our results show a marked reduction of complex-I N-module subunit abundance and an increase in the levels of the assembly factor NDUFA2. Transiently-associated non-mitochondrial proteins such as PKCδ, and the complement subcomponent C1Q were also increased in Ndufs4-deficient mitochondria. Furthermore, lack of Ndufs4 induced ATP synthase complex and pyruvate dehydrogenase (PDH) subunit hyperacetylation, leading to decreased PDH activity. We provide novel insight on the pathways involved in mitochondrial disease, which could underlie potential therapeutic approaches for these pathologies.